2012
DOI: 10.1103/physreva.85.032704
|View full text |Cite
|
Sign up to set email alerts
|

Cross sections for low-energy inelastic Mg + H and Mg++ Hcollisions

Abstract: We report full quantum scattering calculations for low-energy near-threshold inelastic cross sections in Mg + H and Mg + + H − collisions. The calculations include all transitions between the eight lowest adiabatic MgH( 2 + ) molecular states, with the uppermost of those diabatically extended to the ionic molecular state in the asymptotic region. This allows us to treat the excitation processes between the seven lowest atomic states of magnesium in collisions with hydrogen atoms, as well as the ion-pair produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
109
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 38 publications
0
109
0
2
Order By: Relevance
“…Thus, the Drawin formula fails to provide reliable estimates for important inelastic processes in collisions with hydrogen. In the case of Mg, the quantum eight-channel calculations Belyaev et al (2012) provide 28 non-zero crosssections for the endothermic processes (excitation and ion-pair production), while the Drawin formula gives only five nonzero (overestimated) cross-sections for the same 28 transitions (see Barklem et al 2012). This is a general feature of the Drawin formula, as discussed in detail by Barklem et al (2011).…”
Section: Hydrogen Atomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the Drawin formula fails to provide reliable estimates for important inelastic processes in collisions with hydrogen. In the case of Mg, the quantum eight-channel calculations Belyaev et al (2012) provide 28 non-zero crosssections for the endothermic processes (excitation and ion-pair production), while the Drawin formula gives only five nonzero (overestimated) cross-sections for the same 28 transitions (see Barklem et al 2012). This is a general feature of the Drawin formula, as discussed in detail by Barklem et al (2011).…”
Section: Hydrogen Atomsmentioning
confidence: 99%
“…are taken from Barklem et al (2012), which are based on calculations of Belyaev et al (2012); see also Guitou et al (2010Guitou et al ( , 2011. These ab initio quantum chemical calculations on which the scattering calculations are based were obtained using the code MOLPRO (Werner et al 2009) and cover the seven lowest lying states of Mg i and the ground state of Mg ii.…”
Section: Hydrogen Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The ion-pair formation process A * + H → A + + H − should not be confused with the ionization process A * + H → A + + H + e − . Belyaev et al (1999Belyaev et al ( , 2010Belyaev et al ( , 2012, Croft et al (1999b), , Guitou et al (2011) were used for computing the inelastic rates and finally for non-LTE astrophysical applications by Barklem et al (2003), Lind et al (2009), and Mashonkina (2013. It was shown that inelastic atomic collisions are important for non-LTE treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The accurate quantum cross sections were calculated for transitions between many low-lying atomic and ionic states for Na, Li, and Mg + H collisions (Belyaev et al 1999Croft et al 1999b;Guitou et al 2011;Belyaev et al 2012) based on accurate ab initio or pseudopotential quantum-chemical data (Belyaev et al 1999;Guitou et al 2011Guitou et al , 2010Croft et al 1999a;Dickinson et al 1999;Belyaev 2007). The excitation, de-excitation, ion-pair formation, and mutual neutralization processes have been studied in detail.…”
Section: Introductionmentioning
confidence: 99%